Challenges in the management of localized Ewing sarcoma in a developing country. (2nd October 2020) - Totadri, Sidharth; Bansal, Deepak; Rao, K. L. N.; Jain, Richa; Saxena, Akshay Kumar; Kapoor, Rakesh; Samujh, Ram; Trehan, Amita
Abstract: Survival in pediatric Ewing sarcoma (ES) lags in low- and middle-income countries (LMICs). This study analyzed factors contributing to a lower outcome in an LMIC center. A retrospective case review of children with localized ES treated from January 2011 till December 2017 was performed. Neoadjuvant chemotherapy with alternating cycles of vincristine, doxorubicin, cyclophosphamide; and ifosfamide, etoposide was administered 3-weekly for 48 weeks. Reassessment was planned for week 12, followed by local therapy (surgery/radiotherapy or both) tailed by adjuvant chemotherapy. Forty-eight patients with mean age 8 years (range: 0.7–14) were evaluated. Extremity and central axis tumors were seen in 25 (52%) and 23 (48%) patients. Three patients died of neutropenic sepsis and five abandoned therapy. Local therapy included primary surgery, radiotherapy and a combination of surgery and radiotherapy in 7 (16%), 20 (45%) and 17 (39%) patients. The 3-year event-free survival (EFS) and disease-free survival (DFS) for the cohort were 47.7 ± 11% and 57.6 ± 11.2%. Time to local therapy >16 weeks was associated with inferior DFS vs. local therapy administered within 16 weeks [46.6 ± 12.4 vs. 63.9 ± 19.4, p =.046]. Older age, axial site, large size and incomplete surgical resection did not predict relapse/progression. Patients who received wide local excision, as local therapy, had 100% DFS. Coordinated efforts to ensure timely therapy can improve outcome in pediatric ES. Abandonment and treatment-related mortality (TRM) are additional challenges that need to be tackled in LMICs.